A Counseling Mobile App to Reduce the Psychosocial Impact of Human Papillomavirus Testing: Formative Research Using a User-Centered Design Approach in a Low-Middle-Income Setting in Argentina - Szwarc, Lucila (2022)
Fil: Straw, Cecilia. CEDES. Centro de Estudios de Estado y Sociedad. Área de Salud, Economía y Sociedad; Argentina.